Analisis Peta Kekeringan Lahan Pertanian Di Kabupaten Lamongan Menggunakan NDDI (Normalized Difference Drought Index) - Nabilah, Salwa; Faroh, Rifky Aisyatul; Affandy, Nur Azizah; Nisa, Tika Ziadhatin; Wijaya, Bara Ramadani (Fakultas Teknik, Universitas Wiraraja, 2025)
Agricultural land is a natural resource that plays an important role in the continuity of human life. Lamongan is one of the regencies with vast agricultural land, around 80% of the Lamongan Regency area is agricultural land consisting of rice fields and non-rice fields. However, every year Lamongan is hit by drought in several regions. Drought in Lamongan occurs on average around June - October. Several sub-districts in Lamongan are hit by drought, one of the causes of which is low rainfall during the dry season. This study used rainfall data and Landsat 8 satellite imagery with a time span of August - October 2019 - 2023. Landsat 8 imagery was adjusted to the months used, and image processing to obtain drought results in Lamongan Regency using the NDDI (Normalized Difference Drought Index). From the processing, the results obtained in October 2023 were that the area hit by severe drought was Sarirejo District with an area value of 32,490,000 m2 from the total area of ​​Sarirejo District of 47,380,000 m2. Around 68.57% of the Sarirejo District area was hit by severe drought. This study aims to determine the area affected by drought in the Lamongan area. So it can be used for mitigation in future drought disasters.